Patient and Provider Variables Associated with Systemic Treatment of Advanced Prostate Cancer. Issue 4 (July 2019) - Caram, Megan E. V.; Wang, Shikun; Tsao, Phoebe; Griggs, Jennifer J.; Miller, David C.; Hollenbeck, Brent K.; Lin, Paul; Mukherjee, Bhramar
Abstract: Introduction: Six treatments have improved overall survival in men with metastatic castration resistant prostate cancer, each differing in toxicities and cost. We identified patient and provider factors associated with variation in the treatment of men with metastatic castration resistant prostate cancer to identify potential barriers to treatments. Methods: A claims database of commercially insured patients was used to identify patients with prostate cancer treated with abiraterone, enzalutamide, docetaxel, cabazitaxel, sipuleucel-T or radium-223 between 2010 and 2016. Multinomial and binomial logistic regressions were conducted to determine patient and provider factors associated with treatment patterns. Results: Among 5, 575 patients identified, those with a household income greater than $99, 000 were less likely to receive an expensive oral androgen signaling inhibitor (abiraterone or enzalutamide) as first line treatment vs docetaxel compared to patients with a household income less than $50, 000 (OR 0.66, 95% CI 0.48–0.92). African American patients (OR 1.43, 95% CI 1.02–2.01), those who live in the Pacific region vs the South Atlantic (OR 2.68, 95% CI 1.74–4.11), those who received treatment from a urologist vs a medical oncologist (OR 16.05, 95% CI 6.01–42.86) or had preexisting heart failure (OR 1.69, 95% CI 1.18–2.42) were more likely to receive first line oral androgen signaling inhibitors over docetaxel, independent of other factors on multivariable analysis. Conclusions: Clinicians and policy makers should be aware of the potential barriers and provider factors that influence the use of novel therapies among patients with advanced prostate cancer, including the paradoxical effect of income and the substantial effect of provider specialty on first line treatment rendered to patients with metastatic castration resistant prostate cancer.